Neurexin dysfunction in neurodevelopmental and neuropsychiatric disorders: a PRIMSA-based systematic review through iPSC and animal models - Shan, Dan; Song, Yuming; Zhang, Yanyi; Ho, Cheong Wong; Xia, Wenxin; Li, Zhi; Ge, Fenfen; Ou, Qifeng; Dai, Zijie; Dai, Zhihao (Frontiers in Behavioral Neuroscience, 2024)
Abstract Background: Neurexins, essential synaptic proteins, are linked to neurodevelopmental and neuropsychiatric disorders like Autism Spectrum Disorder (ASD) and schizophrenia. Objective: Through this systematic review, we aimed to shed light on the relationship between neurexin dysfunction and its implications in neurodevelopmental and neuropsychiatric manifestations. Both animal and human-induced pluripotent stem cell (hiPSC) models served as our primary investigative platforms. Methods: Utilizing the PRISMA 2020 guidelines, our search strategy involved scouring articles from the PubMed and Google Scholar databases covering a span of two decades (2003-2023). Of the initial collection, 27 rigorously evaluated studies formed the essence of our review. Results: Our review suggested the significant ties between neurexin anomalies and neurodevelopmental and neuropsychiatric outcomes, most notably ASD. Rodent-based investigations delineated pronounced ASD-associated behaviors, and hiPSC models derived from ASD-diagnosed patients revealed the disruptions in calcium dynamics and synaptic activities. Additionally, our review underlined the integral role of specific neurexin variants, primarily NRXN1, in the pathology of schizophrenia. It was also evident from our observation that neurexin malfunctions were implicated in a broader array of these disorders, including ADHD, intellectual challenges, and seizure disorders. Conclusion: This review accentuates the cardinal role neurexins play in the pathological process of neurodevelopmental and neuropsychiatric disorders. The findings underscore a critical need for standardized methodologies in developing animal and hiPSC models for future studies, aiming to minimize heterogeneity. Moreover, we highlight the need to expand research into less studied neurexin variants (i.e., NRXN2 and NRXN3), broadening the scope of our understanding in this field. Our observation also projects hiPSC models as potent tools for bridging research gaps, promoting translational research, and fostering the development of patient-specific therapeutic interventions.